(untitled) (TAMADDUN NURI JURNALI, 2024)
This article discusses the emergence of the Jadidism movement, its spread throughout Turkestan, its main goals and directions. In the course of the article, aspects of the connection between the works created by the Jadids and their period and today, in particular, this the process is illuminated and explained on the basis of Abdulla Qadiri’s works.